Optimization of Ferulic Acid Production From Oil Palm Frond Waste Via Enzymatic Hydrolysis Using Soil Culture - Hafizuddin, Wan Yussof; N., Zainol; Zulsyazwan, Ahmad Khushairi (Institute of Bioproduct Development, Faculty of Chemical and Energy Engineering, Universiti Teknologi Malaysia, 2016)
An enzymatic hydrolysis of fibre-pressed oil palm frond (FPOPF) was carried out using soil culture for ferulic acid production. The soil obtained from palm oil plantation was acclimatized with FPOPF substrate for 30 days before being used as soil culture. FPOPF substrate was prepared with a 1:10 ratio of FPOPF to water. By using Design Expert 7, a central composite design with two factors was selected as the experimental design resulting a total of 13 runs. Two factors studied were temperature (24°C to 28°C) with 26°C as centre point, and agitation rate (130 rpm to 170 rpm) with centre points at 150 rpm. The ANOVA showed that the experimental design model was significant. The coefficient of determination value was 0.8873, indicating that the probability this model was obtained through noise was 11.27%. The optimum condition obtained was temperature at 26°C and agitation rate at 150 rpm with a response of 205.724 mg FA/kg OPF. The optimization was repeatable with a small error of 8.41% from validation test.